ANALISIS KELAYAKAN FINANSIALUSAHA PERIKANAN TAMBAK POLIKULTUR BANDENG-UDANG WINDU (Jurnal Social Economic of Agriculture, 2014)
The purpose of this researchwas to analyze the financial viability of milkfish-tiger shrimp polyculture in sylvofishery ponds in PemangkatSub District and non sylvofishery ponds in Jawai, and Jawai SelatanSub District, Sambas. The research method was survey with 133 fish farmers as respondents. Financial analysis with the criteria of NPV, IRR, B / C, and sensitivity analyis. The results of thisresearch showed polyculture of milkfish - tiger shrimp in Pemangkat, Jawai, andJawai SelatanSub District are financially feasible. Polyculture ponds in the Pemangkat sub district with the application of sylvofishery by 60:40 patterns (60% planted of mangroves and 40% ponds area) provides the highest NPV value of 40,492,764, net B / C of 1.9, and 39.5% IRR , with a return on investment for 3.6 years.   Keywords: polyculture, milkfish-tiger shrimp, financial analysis, mangrove